Research of role of librarian-bibliographical service in the party education system of Shirvintas, Kedainiai and Zarasai district party committees of Lithuania - Тамошюнас, Леонас (Knygotyra, 1983)
Marxist-Leninist education is not only a sphere of large scale activity but is of great ideological-political significance. Lithuanian bibliographical service plays an important role in improving the contents of party education. The activity of political education libraries in Lithuanian republic has not enough been studied yet.The purpose of the programme of library bibliographical service research is to analyse the state of information-bibliographical system in party libraries, to estimate their propaganda technical equipment level, to eveluate how widely party literature and visual aids are used. It is also necessary to take into account the level of library service of readers.A set of factors has been found out by tests. These factors have influence on present state and further development to meet needs of propagandists in party education system. This kind of testing has been held by party education libraries of Shirvintas, Kedainiai and Zarasai district party commitees of Lithuania during 1979.90 questionnaires have been distributed. They include demographical characteristics of propagandists. There are some questions in these questionnaires which help to evaluate the level of usage those libraries and their information-bibliographical service. Test results and some conclusions are covered in this article.